Introduction To The Law Of Indonesia - Sri Hardini (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2016)
The law is derived from the Dutch language . In Dutch, recht order , the arrangement is legal , it means giving rightful place to the law , what is meant by " giving the actual place " that is prepare well and our rule - the rule of law in social life . It was done so that the applicable provisions , can easily be identified and used to resolve any legal event occurs . Therefore , the rule of law is no rule of law at a given moment , a particular place which is called positive law or ius constitutum . The rule of law its kind ever called laws apply and fixed ( recht ).